En-face analysis of the human limbal lymphatic vasculature. (December 2020) - Palme, Christoph; Ahmad, Sajjad; Romano, Vito; Seifarth, Christof; Williams, Bryan; Parekh, Mohit; Kaye, Stephen B.; Steger, Bernhard
Abstract: Purpose: To describe the location and morphometric characteristics of the human limbal lymphatic vasculature and its relation to the marginal corneal vascular arcades (MCA). Methods: Ex vivo confocal microscopic (CM) imaging and immunofluorescence double staining for CD-31 and D2-40 of histological en-face sections using 12 preserved human cadaveric corneoscleral discs were performed, followed by a semi-automated morphometric analysis of the two-dimensional vascular network architecture. Results: Ex vivo CM confirmed the presence of 2 distinct vascular networks. The haematic limbal vascular complex (HLVC) extended further into the cornea, forming typical MCAs. The lymphatic limbal vascular complex (LLVC) was peripheral from the termination of Bowman's layer and was also found to be peripheral to and deeper than the HLVC. LLVC and HLVC were significantly different with respect to vessel diameter, segment length and wall thickness. Conclusion: The lymphatic vasculature of the human corneoscleral limbal region displays specific morphometric features that allow its differentiation from haematic vessels using CM. Highlights: Confocal microscopy lacks validation to image the limbal lymphvasculature. Correlating confocal and immunofluorescence microscopy validates lymphatic imaging. We describe en-face morphological parameters to reliably identify limbal lymphatic vessels using confocal microscopy.